2012
DOI: 10.2519/jospt.2012.3763
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients Achieve Normal Gait Patterns 3 Years After Total Knee Arthroplasty?

Abstract: STUDY DESIGN Longitudinal cross-sectional study. BACKGROUND In the early stages after total knee arthroplasty (TKA), quadriceps strength of the operated limb decreases and is substantially less than that of the nonoperated limb. This asymmetry in strength is related to asymmetrical movement patterns that increase reliance on the nonoperated limb. Over time, quadriceps strength in the operated limb increases but remains less than that in age-matched controls without knee pathology, whereas the quadriceps stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 32 publications
4
51
0
1
Order By: Relevance
“…In contrast, it has been shown previously that individuals post-TKA have significantly less WB during gait on the surgical limb compared to the non-surgical limb (3 months after surgery) and that symmetry improves by 3 years after surgery. 31 With our study sample, the WBRs indicated a high amount of symmetry pre-op, creating a ceiling effect for the amount of change that could occur with intervention. It is evident from our data that although a sub-population of patients have significant WB asymmetry before and early after unilateral TKA, 4, 6, 8, 31 asymmetrical WBR does not characterize all patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In contrast, it has been shown previously that individuals post-TKA have significantly less WB during gait on the surgical limb compared to the non-surgical limb (3 months after surgery) and that symmetry improves by 3 years after surgery. 31 With our study sample, the WBRs indicated a high amount of symmetry pre-op, creating a ceiling effect for the amount of change that could occur with intervention. It is evident from our data that although a sub-population of patients have significant WB asymmetry before and early after unilateral TKA, 4, 6, 8, 31 asymmetrical WBR does not characterize all patients.…”
Section: Discussionmentioning
confidence: 80%
“…31 With our study sample, the WBRs indicated a high amount of symmetry pre-op, creating a ceiling effect for the amount of change that could occur with intervention. It is evident from our data that although a sub-population of patients have significant WB asymmetry before and early after unilateral TKA, 4, 6, 8, 31 asymmetrical WBR does not characterize all patients. Other measures of movement pattern may be superior to WBR for capturing changes in movement quality before and after TKA.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[57] Failure to resolve limitations in quadriceps strength in the early post-operative period can result in residual deficits impacting physical function more than one year following the operative procedure. [5, 7, 8] Interestingly, the relationship between the magnitude of surgical deformity correction and quadriceps strength has yet to be fully elucidated. [9, 10] Previous studies, including those examining the use of computer assisted techniques, have been primarily limited to self-reported outcomes, and fail to capture meaningful declines in quadriceps strength likely to impact function during the early postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are different possible gait adaptations to TKA which are likely not limited to the lower extremity but also include changes in upper body kinematics. However, most studies have focused on lower body kinematics and kinetics and frontal knee moments in people with knee osteoarthritis or patients after TKA [13][14][15]. To the best of our knowledge comprehensive information on ambulatory changes including joint kinetics and joint kinematics of the lower and upper body in patients with good physical function after TKA during walking and stair ascending is lacking.…”
Section: Introductionmentioning
confidence: 99%